A Green & Facile synthesis of diethyl 4-aryl-2,6-bis((arylsulfonyl)methyl)-1,4-dihydropyridine-3,5-dicarboxylate using Montmorillonite K-10 as a catalyst and their antifungal studies - P.S. HARIKRISHNAN (The Bioscan, 2024)
A multicomponent reaction of ethyl-3-oxo-4-(arylsulfonyl)butanoates , aromatic aldehydes and ammonium acetate using Montmorillonite K-10 as a catalyst provided a series of novel diethyl 4-aryl-2,6-bis((arylsulfonyl)methyl)-1,4-dihydropyridine-3,5-dicarboxylate. This synthetic approach provides an example of a green and facile synthesis under mild reaction condition with considerable yield and purity. The compounds synthesised were evaluated for their antifungal studies.